CONCEPTUAL ASPECTS OF ECONOMIC SECURITY OF HIGHER EDUCATION IN THE CONTEXT OF ITS MODERNIZATION - Nikolay Plotnikov (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the process of modernization of the system of higher professional education, unlike the reform process. The author defines the main characteristics of the process depending on the approach to its evaluation. An important consideration in the analysis of the modernisation process is the definition of true goals, which are the driving force in this process.